2022
DOI: 10.1101/2022.08.24.505067
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Ebola virus VP40 matrix undergoes endosomal disassembly essential for membrane fusion

Abstract: Ebola viruses (EBOVs) are filamentous particles, whose shape and stability are determined by the VP40 matrix. Virus entry into host cells occurs via membrane fusion in late endosomes; however, the mechanism of how the remarkably long virions undergo uncoating including virion disassembly and nucleocapsid release into the cytosol, remains unknown. Here, we investigate the structural architecture of EBOVs entering host cells and discover that the VP40 matrix disassembles prior to membrane fusion. We reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Unlike in influenza viruses, arenaviruses do not have proton channels in their lipid envelope that actively acidify the virion upon endocytosis. However, it has been recently shown that protons can also passively cross viral membranes leading to viral matrix reorganization in Ebola virus [56]. Besides the pH-dependent NP-Z interaction, we observed that Z starts to oligomerize between pH 5 and 5.5.…”
Section: Discussionmentioning
confidence: 60%
“…Unlike in influenza viruses, arenaviruses do not have proton channels in their lipid envelope that actively acidify the virion upon endocytosis. However, it has been recently shown that protons can also passively cross viral membranes leading to viral matrix reorganization in Ebola virus [56]. Besides the pH-dependent NP-Z interaction, we observed that Z starts to oligomerize between pH 5 and 5.5.…”
Section: Discussionmentioning
confidence: 60%
“…Alternatively, a theoretical analysis predicted a higher uptake rate of tubular particles over spherical ones ( 89 ), suggesting that endocytosis might be the important step affected by virus shape. Moreover, spherical and tubular virions form in different pathways, resulting in distinct lipid compositions and structures viral matrix layer, which can also affect the fusion rate ( 90 ). Therefore, further research is needed to clarify the relationship between virus shape and infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…In models of pores arising directly from hemifusion stalks, fusion proteins may stabilize the stalk and mechanically drive pore opening, with associations between fusion peptides and TMDs, providing required energy (68,73,110). Changes to the underlying viral matrix may assist pore formation or expansion (111)(112)(113)(114).…”
Section: Focusing On the Membranes: Organization Dynamics And Energet...mentioning
confidence: 99%